A Muscle-Invasive Bladder Cancer Patient With High Tumor Mutational Burden and RB1 Mutation Achieved Bladder Preservation Following Chemotherapy Combined With Immunotherapy: A Case Report - Cao, Chuanzhen; Fu, Zhichao; Liu, Yueping; Zhou, Aiping; Wang, Jianfei; Shou, Jianzhong (Frontiers in Immunology, 2021)
Neoadjuvant chemotherapy followed by radical cystectomy is the standard of care for patients diagnosed with muscle-invasive bladder cancer (MIBC). However, urinary diversion following radical cystectomy significantly reduces patient quality of life. In addition, patients who significantly respond to neoadjuvant chemotherapy have a strong will to preserve the bladder. Bladder-sparing therapy has become a research focus worldwide. Although the bladder-sparing regimen, referred to as trimodality therapy (TMT), has been accepted, the efficacy of immunotherapy combined with chemotherapy for bladder preservation in patients with MIBC has not yet been published. We describe the case of a 50-year-old male presented intermittent macrohematuria and was diagnosed with bladder urothelial carcinoma by diagnostic transurethral resection of bladder tumor (TURBt) with clinical stage IIIA (cT3bN0M0). A complete response was achieved after four courses of neoadjuvant chemotherapy combined with pembrolizumab. Then, we performed a second TURBt plus randomized biopsy by cystoscopy. The pathology indicated no tumor in the bladder. Adjuvant chemoradiotherapy and immunotherapy were subsequently performed. Imaging examinations, cystoscopy and urine tumor DNA (utDNA) levels were used for surveillance after treatment. Finally, the patient achieved bladder preservation and had remained cancer-free for 19 months at the last follow-up on February 20, 2021. This is the first published case study to describe neoadjuvant chemotherapy plus pembrolizumab followed by concurrent chemoradiotherapy as a novel bladder-sparing regimen and successfully achieved a promising outcome.